Faktor – Faktor Penyebab Anemia yang Terjadi Pada Remaja Putri di SMK Jakarta Timur 2 Kelurahan Cakung Timur Kecamatan Cakung - Nurmaliyati, Nurni; Istiqomah, Istiqomah (Universitas Malahayati, 2025)
ABSTRACT The prevalence of anemia in the world ranges from 40 - 88%. The prevalence of iron deficiency anemia in adolescent girls in Indonesia is 22.7%. (Ministry of Health of the Republic of Indonesia, 2021). Meanwhile, data on the achievement of anemia in adolescent girls from the DKI Jakarta Provincial Health Office in 2023 was 48.30%. Then in the same year in the Cakung Health Center area, it was 56.75%, where one of the areas with a fairly high anemia rate was the Cakung Timur Village area of 54.01%.this study aims to determine the Factors Causing Anemia That Occurs in Adolescent Girls at SMK Jakarta Timur 2, Cakung Timur Village, Cakung District. This study is a type of quantitative research using a cross-sectional approach. The population in this study were 190 grade 10 female students of SMK Jakarta Timur 2, Cakung Timur Village, Cakung District, with a sample of 64 female students using random sampling. The data types are primary and secondary data. Data analysis uses univariate and bivariate analysis using chi square correlation. Based on the chi-square test, it was found that there was no significant relationship between parental education (p = 0.272), knowledge (p = 0.200), menstrual status (p = 0.066), menstrual cycle (p = 0.157), duration of menstruation (p = 0.463), menstrual volume (p = 0.117), consumption of Fe tablets (p = 0.536), number of Fe tablets consumed (p = 0.568) on the incidence of anemia in adolescent girls, it was found that there was a significant relationship between the status of iron tablet consumption on the incidence of anemia in adolescent girls (p = 0.047) with an OR value of 4.063 (0.966-17.091. The research that has been conducted at SMK Jakarta Timur 2, Cakung Timur Village, Cakung District, obtained that 45% of adolescent girls suffer from anemia. Factors such as parental occupation, level of knowledge and menstruation according to the adolescent girls who were respondents were not factors that caused anemia in adolescent girls. Keywords: Factors, Anemia, Adolescent Girls. ABSTRAK Prevalensi anemia di dunia berkisar antara 40 – 88%. Prevalensi anemia gizi besi pada remaja putri di Indonesia sebesar 22,7%. (Kemenkes RI, 2021). Sementara data capaian anemia remaja putri dari Dinas Kesehatan Provinsi DKI Jakarta tahun 2023 sebesar 48.30%. Lalu pada tahun yang sama di wilayah Puskesmas Cakung, sebesar 56,75%, dimana salah satu wilayah dengan angka anemia yang cukup tinggi adalah wilayah Kelurahan Cakung Timur sebesar 54,01%. Penelitian ini yaitu bertujuan untuk mengetahui Faktor - Faktor Penyebab Anemia Yang Terjadi Pada Remaja Putri Di SMK Jakarta Timur 2 Kelurahan Cakung Timur Kecamatan Cakung. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah siswi kelas 10 SMK Jakarta Timur 2 Kelurahan Cakung Timur Kecamatan Cakung sebanyak 190, sampel sebanyak 64 orang siswi dengan random sampling. Jenis data adalah data primer dan sekunder Analisis data menggunakan analisis univariat dan bivariat menggunakan korelasi chi square. Berdasarkan uji chi-square, didapatkan hasil tidak ada hubungan bermakna antara pendidikan orang tua (p=0,272), pengetahuan (p=0,200), status menstruasi (p=0,066), siklus menstruasi (p=0,157), lama menstruasi (p=0,463), volume menstruasi (p=0,117), konsumsi tablet Fe (p=0,536), jumlah konsumsi tablet Fe (p=0,568) terhadap kejadian anemia remaja putri, didapatkan hasil ada hubungan bermakna antara status konsumsi tablet tambah darah terhadap kejadian anemia remaja putri (p=0,047) dengan nilai OR 4.063 (0.966-17.091. Penelitian yang telah dilakukan di SMK Jakarta Timur 2 Kelurahan Cakung Timur Kecamatan Cakung diperoleh sebanyak 45% remaja putri menderita anemia. Faktor-faktor seperti pekerjaan orang tua, tingkat pengetahuan dan menstruasi menurut para remaja putri yang dilakukan sebagai responden bukanlah faktor yang menyebabkan kejadian anemia pada remaja putri. Kata Kunci: Faktor – Faktor, Anemia, Remaja Putri.